Ablation of Pyrophosphate Regulators Promotes Periodontal Regeneration. (June 2021) - Nagasaki, A.; Nagasaki, K.; Chu, E.Y.; Kear, B.D.; Tadesse, W.D.; Ferebee, S.E.; Li, L.; Foster, B.L.; Somerman, M.J.
Biomineralization is regulated by inorganic pyrophosphate (PPi ), a potent physiological inhibitor of hydroxyapatite crystal growth. Progressive ankylosis protein (ANK) and ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) act to increase local extracellular levels of PPi, inhibiting mineralization. The periodontal complex includes 2 mineralized tissues, cementum and alveolar bone (AB), both essential for tooth attachment. Previous studies demonstrated that loss of function of ANK or ENPP1 (reducing PPi ) resulted in increased cementum formation, suggesting PPi metabolism may be a target for periodontal regenerative therapies. To compare the effects of genetic ablation of Ank, Enpp1, and both factors concurrently on cementum and AB regeneration, mandibular fenestration defects were created in Ank knockout ( Ank KO), Enpp1 mutant ( Enpp1 asj/asj ), and double KO (dKO) mice. Genetic ablation of Ank, Enpp1, or both factors increased cementum regeneration compared to controls at postoperative days (PODs) 15 and 30 ( Ank KO: 8-fold, 3-fold; Enpp1 asj/asj : 7-fold, 3-fold; dKO: 11-fold, 4-fold, respectively) associated with increased fluorochrome labeling and expression of mineralized tissue markers, dentin matrix protein 1 ( Dmp1 /DMP1), osteopontin ( Spp1 /OPN), and bone sialoprotein ( Ibsp /BSP). Furthermore, dKO mice featured increased cementum thickness compared to single KOs at POD15 and Ank KO at POD30. No differences were noted in AB volume between genotypes, but osteoblast/osteocyte markers were increased in all KOs, partially mineralized osteoid volume was increased in dKO versus controls at POD15 (3-fold), and mineral density was decreased in Enpp1 asj/asj and dKOs at POD30 (6% and 9%, respectively). Increased numbers of osteoclasts were present in regenerated AB of all KOs versus controls. These preclinical studies suggest PPi modulation as a potential and novel approach for cementum regeneration, particularly targeting ENPP1 and/or ANK. Differences in cementum and AB regeneration in response to reduced PPi conditions highlight the need to consider tissue-specific responses in strategies targeting regeneration of the entire periodontal complex.